EFEKTIVITAS PENYELESAIAN TINDAK PIDANA PERZINAHAN YANG DILAKUKAN SECARA HUKUM ADAT - Fikarman Bawamenewi (Jurnal Panah Hukum, 2023)
Adultery is intercourse between a man and a woman who are not bound by marriage or marriage. The crime of adultery is an act that cannot be committed by anyone for any reason. One of the criminal acts of adultery that occurred in Hilisao'oto Village was resolved according to custom, the perpetrator was sentenced to a customary sanction, namely a fine of Rp. 3,000,000.00 and 2 pigs. In the settlement of adultery cases, especially in Hilisao'oto Village, Sidua'ori District, South Nias Regency, they still go through a customary deliberation process where the settlement method is carried out based on the absolute decision of the parties concerned, starting from the customary elders, community leaders and village officials. The type of research used is a type of sociological research with an empirical method that examines and analyzes individual legal actors and community groups in relation to the law. The data analysis used was descriptive qualitative data analysis and conclusions were drawn using the deductive method. Based on the research findings and discussion, it can be concluded that the effectiveness of the settlement was proven by the absence of objections from both parties so far, in this settlement the victim also promised not to object to the perpetrator at a later time. The author suggests that in this case the policy makers in Hilisao'oto Village are more burdensome in fines and sanctions for each perpetrator of the crime of adultery, more specifically in terms of financial fines so as to be able to provide a deterrent effect for every perpetrator of the crime of adultery that applies in Hilisao'oto Village. Customary law provisions must be made in writing in the form of village regulations so that there is certainty of punishment for each perpetrator of the crime of adultery